Gonad maturity level and somatic index of sea cucumber Acaudina sp. (caudinidae, molpadida, holothuroidea) In Delta Wulan Waters, Demak Regency, Indonesia. Issue 1 (November 2021) - Widianingsih, W; Hartati, R; Sibero, M T; Mahendrajaya, R T
Abstract: Sea cucumber Acaudina sp. belongs to the family Caudinidae, Order Molpadida, Class Holothuroidea. These animals have an important role in the benthic ecosystem. The purpose of this research was to determine the gonad maturity level and Gonad Somatic Index of Acaudina sp. in Delta Wulan Waters, Demak Regency. In total, 64 individuals of Acaudina sp. were taken in April 2021 and 148 individuals were taken in May 2021. In April observation, the highest gonad maturity level for females was at level 3, while the highest gonad maturity for male was at levels 1 and 2. Furthermore, in Mei observations, the highest gonad maturity level for females was at level 2 and for males, the highest gonad maturity level was at level 3. According to April observation, values GSI (Gonad Somatic Index) has a range 0.22 - 6.09 % and for May observation, value GSI has a range 0.04 – 2.24%. Hence, there is a positive correlation between gonad weight and GSI values in sea cucumber Acaudina sp.